A review on machining of carbon fiber reinforced ceramic matrix composites. Issue 15 (15th October 2019) - Du, Jinguang; Zhang, Haizhen; Geng, Yongmiao; Ming, Wuyi; He, Wenbin; Ma, Jun; Cao, Yang; Li, Xiaoke; Liu, Kun
Abstract: Carbon fiber reinforced ceramic matrix ceramic/polymers composites have excellent physical-mechanical properties for their specific strength, high hardness, and strong fracture toughness relative to their matrix, and they also possess a good performance of wear resistance, heat resistance, dimensional stability, and ablation resistance. It is a choice for thermal protection and high temperature structural materials. However, this kind of composites owning characteristics of high hardness and abrasion is difficult to machine which impedes the large-scale industrial application of manufacturing. This paper mainly reviews the research on machining status of carbon fiber reinforced ceramic matrix composites including carbon fiber reinforced polymer matrix composites from the aspects of conventional machining and unconventional machining method. The machining trends, problems existing in various machining methods and corresponding solutions are generalized and analyzed.